Newborn screening for severe combined immunodeficiency: lessons from a pilot study and prospects - O.R. Boyarchuk; N.M. Yarema; H.V. Makukh (Zaslavsky O.Yu., 2023)
The expansion of the neonatal screening program in Ukraine from October 2022 became an important achievement in the development of domestic medicine. Despite the severe challenges of the war and the burden of the COVID-19 pandemic, Ukraine was able to reach the level of the leading European countries, in which screening of newborns covers more than 20 disorders. Severe combined immunodeficiencies (SCID) are among the diseases included in the program of expanded mass screening of newborns. In this article, the authors focus on the challenges they faced during the implementation of the first pilot project in Ukraine on newborn screening for severe combined immunodeficiencies using TREC and KREC assay. The method allows to determine not only SCID, but also other conditions that occur with T- and/or B-lymphopenia, which can be considered both an advantage and a disadvantage of the method, because it requires to set the certain level of cutoff. The urgency of the investigation is critically important for SCID screening. Therefore, organizational issues and the coordinated functioning of the entire screening program are of decisive importance. The conducted analysis, considering our own experience and data of other studies, outlined the issues that need to be resolved in the further implementation of screening for SCID. Improvement of the screening algorithm (with clarifying examinations when taking the second sample, or genetic examination of the SCID panel already from the first sample); determining the path of a patient with a positive TREC result; solving the issue of measuring the lymphocyte subsets by flow cytometry at the regional centers; issues of BCG vaccination and prevention of cytomegalovirus infection; conducting trainings with doctors involved in the screening program; sharing the information among the medical community and the public will improve the newborn screening program for SCID, shorten the patient's path to diagnosis, which in the end may have a positive impact on the quality of life and life expectancy of those with severe T- and/or B-lymphopenia.